2018
DOI: 10.1038/s41598-018-32213-8
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to obtain pure and active proteins from Lactococcus lactis protein aggregates

Abstract: The production of pure and soluble proteins is a complex, protein-dependent and time-consuming process, in particular for those prone-to-aggregate and/or difficult-to-purify. Although Escherichia coli is widely used for protein production, recombinant products must be co-purified through costly processes to remove lipopolysaccharide (LPS) and minimize adverse effects in the target organism. Interestingly, Lactococcus lactis, which does not contain LPS, could be a promising alternative for the production of rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Soluble MMP-9 was obtained from the solubilization of MMP-9 IBs produced in L. lactis, as previously described [12]. Briefly, bacteria were suspended (30:500 PBS:culture, volume) and disrupted for 4 rounds by French press, at 1500 psi, ice-coated, and with protease inhibitors (Complete EDTA-free, Roche), followed by a 2 h incubation in 0.05 mg/mL of lysozyme, at 37 • C, in agitation.…”
Section: Production and Purification Of Soluble Mmp-9mentioning
confidence: 99%
See 1 more Smart Citation
“…Soluble MMP-9 was obtained from the solubilization of MMP-9 IBs produced in L. lactis, as previously described [12]. Briefly, bacteria were suspended (30:500 PBS:culture, volume) and disrupted for 4 rounds by French press, at 1500 psi, ice-coated, and with protease inhibitors (Complete EDTA-free, Roche), followed by a 2 h incubation in 0.05 mg/mL of lysozyme, at 37 • C, in agitation.…”
Section: Production and Purification Of Soluble Mmp-9mentioning
confidence: 99%
“…In most cases, IBs have been produced by using Escherichia coli as recombinant cell factory; however, their production has also been successfully done in lipopolysaccharide (LPS)-free recombinant systems, such as Lactococcus lactis [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Samples were tested for sterility by plating an aliquot in agar-M17 plates with 0.5% glucose and incubating them overnight at 30 °C. Aliquots of rMMP-9 IBs and mutant inactive rMMP-9 IBs were tested for purity through SDS-PAGE electrophoresis and Coomassie blue staining (75.7% purity obtained for MMP-9 IBs and 70.3% for mutMMP-9 IBs), and were quantified by interpolation with the bands obtained by a solubilized rMMP-9 as the standard 28 , using ImageJ software (version 1.46r, U. S. National Institutes of Health, Bethesda, Maryland, USA). The activity of the MMP-9 IBs and the inactivity of the mutMMP-9 IBs, were validated in vitro both by zymography and DQgelatin (data not shown).…”
Section: Purification Of Ibsmentioning
confidence: 99%
“…Skimmed MGS were quantified for endogenous MMP-9 activity through zymography analysis. Solubilized MMP-9 28 was used to prepare an eight-point standard curve ranging from 400 to 25 ng. Sample supernatants were diluted 1/10 and diluted samples and standards were loaded with non-denaturing loading buffer into 10% SDS-PAGE gels containing 1% porcine gelatine.…”
Section: Mammary Secretion Analyses Somatic Cell Counts Half ML Of mentioning
confidence: 99%
“…The classic view of protein aggregates as mere inactive folding intermediates has been transformed into the idea of heterogeneous porous multimeric structures stabilized by a scaffold of cross beta-sheet structures that contain conformers of the recombinant protein in which a spectrum of recombinant protein species containing native-like conformations are incorporated [12]. In fact, it has been proven that biologically active protein species can be extracted from IBs by applying mild solubilization protocols, indicating the biologically active nature of proteins forming these aggregates [24]. In addition, further ground-breaking studies have suggested applications of IBs in nanomedicine.…”
mentioning
confidence: 99%